A metamorfose dos partidos com origem na classe trabalhadora: o caso do PT no Brasil - Cignachi, Henrique (2013)
This work central object is the process of metamorphosis of political parties originated in the working class, especially the process of metamorphosis of the Workers Party (PT) in Brazil. By employing methodological and theoretical Marxist about politics and social classes, we tried to present the main interpretations of the metamorphosis of the european social democracy, understood as the classical model of transformation of workers party from a radical source to a consensus model, pro-systemic. By analyzing the history of the evolution of political organizations of the brazilian working class was possible to diagnose that PT represented successive breaks with past models (PTB and PCB), although in its evolution it has approached in strategic reading and in the federal government very close of those. From a radical party the Workers Party has become a party of government, seeking to establish a consensus, a "compromise" between social classes, which leads us to characterize the PT as an example of a contemporary social democratic party. However, if the european social democratic consensus was given by the approximation with the "petty bourgeoisie", in Brazil he was through with the approach of "sub-proletariat." Thus, both sectors have functional characteristics for the neutralization of radical proposals in bourgeois society, despite the distance between both.